FACTORS THAT INFLUENCE THE ADEQUACY OF DIALYSIS IN PATIENTS UNDERGOING DIALYSIS THERAPY AT THE HEMODIALISIS INSTALLATION OF HOSPITAL dr. ZAINOEL ABIDIN IN 2023 - Leli Alasta; Gadis Halizasia; Ferdi Riansyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Chronic kidney failure is a disease that requires hemodialysis. Long-term hemodialysis therapy will affect various aspects of life and have an impact on reducing the patient's quality of life. To improve the patient's quality of life, this can be done by increasing the patient's adequacy in each hemodialysis session. The study aimed to identify factors that influence dialysis adequacy in patients undergoing dialysis therapy in the hemodialysis installation at RSUD dr. Zainoel Abidin. This type of research is descriptive correlative with a cross-sectional study design. The population in this study were chronic kidney failure patients undergoing hemodialysis. Sampling used the Slovin formula purposive sampling technique, namely 85 respondents. The data collection tool is a standard table with the Cronin scale. Univariate and bivariate analysis data. The results of the bivariate analysis show that there is a relationship between Quick of Blood (QB) and hemodialysis adequacy with a p-value = 0.001 (P < 0.005), there is a relationship between time of dialysis and hemodialysis adequacy with a p-value = 0.001 (p < 0.001), there is the relationship between vascular access and hemodialysis adequacy with P-value=0.004 (p<0.005).